2014
DOI: 10.1038/ncomms5588
|View full text |Cite
|
Sign up to set email alerts
|

The condensin component NCAPG2 regulates microtubule–kinetochore attachment through recruitment of Polo-like kinase 1 to kinetochores

Abstract: The early event of microtubule-kinetochore attachment is a critical stage for precise chromosome segregation. Here we report that NCAPG2, which is a component of the condensin II complex, mediates chromosome segregation through microtubule-kinetochore attachment by recruiting PLK1 to prometaphase kinetochores. NCAPG2 colocalizes with PLK1 at prometaphase kinetochores and directly interacts with the polo-box domain (PBD) of PLK1 via its highly conserved C-terminal region. In both humans and Caenorhabditis elega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 57 publications
(103 reference statements)
0
39
0
Order By: Relevance
“…Mouse ESCs were karyotyped as described . Briefly, cells were harvested after 6 hours of colcemid (100 ng/ml) treatment and incubated sequentially in a hypertonic solution (0.075 M KCl) and a fixing solution (methanol/acetic acid, 3:1).…”
Section: Methodsmentioning
confidence: 99%
“…Mouse ESCs were karyotyped as described . Briefly, cells were harvested after 6 hours of colcemid (100 ng/ml) treatment and incubated sequentially in a hypertonic solution (0.075 M KCl) and a fixing solution (methanol/acetic acid, 3:1).…”
Section: Methodsmentioning
confidence: 99%
“…Abnormal condensin distribution on mitotic chromosomes correlated with diminished Plk1 enrichment at pericentromeric regions. A previous study on human cells showed that stable localization of Plk1 to the kinetochores requires an interaction with the condensin II subunit Ncapg2 (Kim et al, 2014). Plk1 is required for stabilizing kinetochore-microtubule attachments by counteracting the spindle assembly checkpoint function of Aurora B (Suijkerbuijk et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Condensins are phosphorylated by Cdk1, Plk1 and Aurora B kinases to ensure proficient chromosome condensation (Abe et al, 2011;Lipp et al, 2007;Tada et al, 2011). In addition, condensins are required for appropriate localization of Aurora B and Plk1 kinases during the prophase-to-metaphase transition and ensure accurate chromosome segregation (Abe et al, 2011;Kim et al, 2014;Green et al, 2012;Kitagawa and Lee, 2015). Components of the Smc5/6 complex have been reported to be phosphorylated by Plk1 and Aurora B kinases during mitosis (Hegemann et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In 2014, Kim et al . found that NCAPG2 interacts with Polo‐like kinase 1 (PLK1) during the prometaphase–metaphase transition during mitosis and was a new critical player in PLK1 kinetochore localization. NCAPG2 localization and PLK1 recruitment to the kinetochores of misaligned chromosomes are critical for the completion of proper chromosome alignment.…”
Section: Introductionmentioning
confidence: 99%